HUBUNGAN FAKTOR PELAYANAN PERTAMA PADA WARGA TERPAPAR COVID DENGAN KESIAPAN BERADAPTASI PADA COVID-19 - Kiana Alif Fatwa Supendi (RSPI PROF. DR. SULIANTI SAROSO, 2023)
The whole world is currently facing tremendous challenges in the system of first care for people who have been exposed to COVID-19 in the community. The rapid transmission of the COVID-19 virus has made people not prepare themselves for first aid. To be able to strengthen and prepare various preparedness strategies to deal with various kinds of viruses that are starting to develop. The readiness of first aid services is needed for residents exposed to COVID-19. The purpose of this study was to determine whether there was a relationship between the first service factor for residents exposed to COVID and readiness to adapt to COVID-19. The method used in this study is a cross sectional approach. The population of this study were all people in RW X Pamulang Timur, South Tangerang who were positive for COVID-19. The number of samples that met the inclusion criteria were 231 people. Data collection was carried out offline by coming directly to the homes of residents who had been exposed to COVID-19 in December 2021 to March 2022. The results of the bivariate analysis obtained a p-value of 0.000 (<ɑ 0.05), so it can be concluded that there is a significant relationship between the first service factor and readiness to adapt to the COVID-19 incident. Keywords: adaptation; covid-19; health services; readiness